The impact of ultrasound-guided erector spinae plane block combined with paravertebral block on postoperative rebound pain following thoracoscopic lobectomy - Yihang He; Dongxu Chen; Youbo Zuo; Jing Lin (Frontiers in Medicine)
BackgroundThoracic paravertebral block (TPVB) is the mainstream analgesic regimen for post-video-assisted thoracoscopic surgery (VATS) pain management. However, rebound pain frequently emerges once the block effect subsides. Given that the erector spinae plane block (ESPB) may modulate the incidence of rebound pain through its mechanism of local anesthetic diffusion into the paravertebral space, this study sought to evaluate whether combining TPVB with ESPB could effectively reduce postoperative rebound pain in VATS patients.MethodsA total of 110 patients scheduled for elective video-assisted thoracoscopic lobectomy were enrolled and randomly allocated via a random number table to either the TPVB group (Group P, n = 55) or the TPVB combined with ESPB group (Group PE, n = 55). In Group P, TPVB was performed under oblique axial scanning at the T5 level using the in-plane technique, with 20 mL of 0.5% ropivacaine administered. In Group PE, TPVB was first performed with 10 mL of 0.5% ropivacaine; the needle was then withdrawn and repositioned with its tip deep to the erector spinae muscle at the transverse process level, followed by injection of 10 mL of 0.5% ropivacaine for ESPB. The primary outcome was the incidence of rebound pain within 24 h postoperatively. Secondary outcomes included: Numeric Rating Scale (NRS) scores at rest (quiet supine position) and during activity (coughing and expectoration) on postoperative day 1 morning (D1 am), evening (D1 pm), day 2 morning (D2 am), and evening (D2 pm); time to first rebound pain within 24 h; Modified Rebound Pain Scale (MRPS) score; Quality of Recovery-15 (QoR-15) scores on postoperative days 1 and 2; total sufentanil consumption via patient-controlled intravenous analgesia (PCIA) over 48 h; number of rescue analgesia doses administered in the ward; postoperative hospital stay; patient satisfaction score at discharge; and postoperative complication rate.ResultsCompared with Group P, Group PE had a significantly lower incidence of rebound pain within 24 h postoperatively (23.64% vs. 47.27%, p = 0.010) and a significantly reduced MRPS score (3.06 ± 1.75 vs. 3.84 ± 2.05; p = 0.035). Additionally, Group PE had lower activity-related NRS scores on D1 am (p = 0.010), D1 pm (p < 0.001), and D2 pm (p = 0.031), as well as a lower resting NRS score on D1 am (p = 0.048). Furthermore, Group PE showed higher QoR-15 scores on both postoperative days 1 and 2 (p < 0.05), reduced 48-h PCIA sufentanil consumption (p = 0.002), fewer rescue analgesia requirements (p = 0.048), and a shorter postoperative hospital stay (p < 0.001).ConclusionCompared with TPVB alone, the combination of TPVB and ESPB significantly reduces the incidence of postoperative rebound pain, prolongs analgesic duration, and improves the quality of postoperative recovery.